Water scarcity and managing seasonal water crisis: lessons from the Kirindi Oya Project in Sri Lanka - Sakthivadivel, Ramaswamy; Loeve, R.; Amarasinghe, Upali A.; Hemakumara, M. (International Water Management Institute, 2001)
Coping with scarcity of water supply for managing irrigation under uncertain and inadequate conditions has become part and parcel of many irrigation systems in the semiarid tropics of Asia. Based on a case study of the Kirindi Oya Irrigation and Settlement Project (KOISP) in southern Sri Lanka, this report provides evidence of the uncertain and inadequate inflow into the reservoir and its impact on the seasonal planning.